The Effect of Preceptorship Training on New Nurse’s Adaptation During Orientation at a Private Hospital in Medan - Tambunan, Dior; Harahap, Sridama Yanti (Jurnal Kesehatan LLDikti Wilayah 1 (JUKES), 2024)
Preceptorship is a specialized area that prepares new recruited nurses and students to integrate previously acquired knowledge with skills and competencies from dependent supervised practice to independent collaborative practice. The study objective is to identify the effect of preceptorship training on new nurses adaptation during orientation. The research method is Pre-Experimental design in one group pretest-posttest without control and 37 respondents with purposive sampling technique. The result showed that pretest scoring of preceptorship training that majority PPA was poor and majorty PS, SC, and CCDTI were fair. While the posttest scoring of preceptorship training was increased significantly as followed: majority PPA was good (70.3%), majorty PS was good (67.6%), majority SC was good (59.5%), and majority CCDTI was good (83.8%) and a meaningful effect with p-value 0.000 (? <0.05). It can be concluded that there was a meaningful effect of Preceptorship Training on New Nurse’s Adaptation During Orientation. Optimal preceptorship will build interpersonal relationships between new and senior nurses, good communication, create a conducive work environment, reduce stress that can reduce the tendency to quit in the middle of the orientation period. It is hoped that further researchers will add variables of turnover intention, burnt out, self-efficacy and work stress.